The displacement effect of pitot tubes in narrow wakes at subsonic and supersonic speeds - Marson, G. B. (College of Aeronautics, Cranfield, 1956)
The apparent displacement of the effective centre of a circular pitot tube from it geometric centre when placed in narrow wakes has been measured at sub and super- sonic speeds. Similar effects were found at all speeds. Continues...